(3ef cJGH GdedIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s
(3ChdgG (B:s
(3hGdedI gi BQGA hCaYGd ebOQI ebjOI HTQGFW jQSegG ddLejY hjJSge GdChd jdJeS Cf jbGd HESJYeGdge dgG ZQVkG dg s
(3BNQgG (B:s
(3cja jchf hMi Gddg JYGdi Edi GdEfSGf GdPi jhMi Edgj hcja jMUd ai GdEfSGf GdbhI Yf GdhMi hGdehMi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B18s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B313 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B267s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs